2015
DOI: 10.1371/journal.pone.0128364
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Small Molecule Inhibitors of Oncogenic RET Kinase

Abstract: Oncogenic mutation of the RET receptor tyrosine kinase is observed in several human malignancies. Here, we describe three novel type II RET tyrosine kinase inhibitors (TKI), ALW-II-41-27, XMD15-44 and HG-6-63-01, that inhibit the cellular activity of oncogenic RET mutants at two digit nanomolar concentration. These three compounds shared a 3-trifluoromethyl-4-methylpiperazinephenyl pharmacophore that stabilizes the ‘DFG-out’ inactive conformation of RET activation loop. They blocked RET-mediated signaling and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“… 24 Studies from our laboratory using cell line and mouse models of non-small cell lung cancer confirmed EphA2 targeting. 22 , 23 A more recent study, however, reported that ALW-II-41-27 inhibits RET tyrosine kinase activity and function in RET-transformed fibroblasts, HEK293 cells, and in primary tumor cells and cell lines from human thyroid cancer, 25 raising the possibility that this inhibitor could impair TNBC growth in our models by targeting other kinases. Since no other group to our knowledge has tested the potential off-target effects in an EphA2-null model, we decided to test the impact of ALW-II-41-27 on EphA2-deficient C3-TAg tumor cells relative to NG-25 analog control.…”
Section: Resultsmentioning
confidence: 90%
“… 24 Studies from our laboratory using cell line and mouse models of non-small cell lung cancer confirmed EphA2 targeting. 22 , 23 A more recent study, however, reported that ALW-II-41-27 inhibits RET tyrosine kinase activity and function in RET-transformed fibroblasts, HEK293 cells, and in primary tumor cells and cell lines from human thyroid cancer, 25 raising the possibility that this inhibitor could impair TNBC growth in our models by targeting other kinases. Since no other group to our knowledge has tested the potential off-target effects in an EphA2-null model, we decided to test the impact of ALW-II-41-27 on EphA2-deficient C3-TAg tumor cells relative to NG-25 analog control.…”
Section: Resultsmentioning
confidence: 90%
“…The majority of TKIs tested until now are multitarget therapies14 15 26 but only a few of them are active against RET . Some new products with a high specificity for several oncogenic RET mutants and chimeric oncogenes have been recently reported,27 28 thus highlighting the necessity to screen for somatic RET mutations, possibly all MTC, or at least those presenting as advanced cases, which are potentially treatable with TKI.…”
Section: Discussionmentioning
confidence: 99%
“…While these agents are nonspecific, they have been investigated in RETdriven NSCLC with response rates as high or higher than with chemotherapy, although lower than that of other oncogenetargeted therapies in NSCLC such as those for EGFR, ALK, ROS1, and BRAF V600E (24)(25)(26). Gatekeeper RET V804M/L mutations may be acquired after targeting of RET fusions with vandetanib or cabozantinib; however, their prevalence in a clinical setting is not known (27)(28)(29)(30). More selective RET inhibitors are showing promise in early-phase clinical trials in patients with RET-driven advanced solid tumors and also have activity against the V804 gatekeeper mutation (NCT03157128, NCT03037385, NCT01877811; refs.…”
Section: Introductionmentioning
confidence: 99%